Agronomic evaluation of plantains and other triploid banana - Baiyeri, K.; Ortíz, R. (International Society for Horticultural Science, 2000)
The agronomic potential of landraces and cultivars must be determined for an optimal utilization of genetic resources in Musa improvement. Field assessment of 75 plantain landraces and 17 banana cultivars was carried out in two representative locations in Nigeria: Onne (southeastern humid lowland forest), and Ibadan (western forest-savanna transition). There were significant differences between the landraces and cultivars for all characteristics. Plant height and girth, height of the tallest sucker at flowering and at harvest, bunch weight, average fruit weight and number of fruit in the third hand were significantly influenced by the genotype-by-location interaction. Number of hands and fruit per bunch, and number of fruit of the first hand were not affected by neither the location nor the genotype-by-location interaction. The number of fruit in the second hand showed the lowest coefficient of variation, which suggests that this characteristic may be more reliable for characterization of Musa germplasm. The significant genotype-by-location interaction for the agronomic characteristics shows the need to identify environmentally representative locations for in situ conservation of Musa germplasm, as well as for its further characterization.